Historical Record of the Seventieth, or, the Surrey Regiment of Foot : Containing an account of the formation of the regiment in 1758, and of its subsequent services to 1848 - Cannon, Richard, 1779-1865 (Salt Lake City, UT : Project Gutenberg, 2021)
"Historical Record of the Seventieth, or, the Surrey Regiment of Foot" by Richard Cannon is a historical account written in the mid-19th century. This book chronicles the formation and military service of the Surrey Regiment from its establishment in 1758 through its later actions up until 1848. The likely topic of the book revolves around the regiment's operational history, including its battles, movements, and the experiences of its officers and soldiers during various conflicts. The narrative details the origin of the Seventieth Regiment as a formation from the second battalion of the Thirty-first Regiment. It outlines the regiment's deployments, notable engagements during the Seven Years' War, its operations in North America during the American Revolutionary War, and service in the West Indies. It also highlights key leaders within the regiment, recounting their promotions and contributions to its legacy. The text serves both as a tribute to the soldiers of the regiment and as a historical document that offers insights into the broader military history of Britain during this period. (This is an automatically generated summary.)
Release date is 2021-11-12
Brian Coe, John Campbell and the Online Distributed Proofreading Team at https://www.pgdp.net (This book was produced from images made available by the HathiTrust Digital Library.)
Keywords: Great Britain. Army -- History; Great Britain. Army. Regiment of Foot, 70th (Surrey)